FEM-based modelling of NSM-FRP bond behaviour - Sharaky, I. A. (2013)
Bond between Fibre Reinforced Polymer (FRP) Near-Surface Mounted (NSM) reinforcement and concrete is one of the key factors affecting the behaviour of this strengthening methodology. Properties of FRP, adhesive and concrete greatly affect the effectiveness of the NSM technique. Due to the variety of factors involved in the behaviour of FRP NSM strengthening systems, mechanical models able to incorporate the influencing variables acquire major importance for the prediction of the load capacity and the contribution of the different parameters. By predicting the results obtained in experimental direct pullout tests, a finite element model is adopted to assess the influence of relevant parameters on bond behaviour, namely: bar type, bar size, bond length, epoxy properties and concrete strength. The finite element approach considers interface finite elements for modelling the bond between FRP reinforcement and concrete, and a smeared crack model to simulate the crack initiation and propagation in the surrounding concrete.